Melampaui Pemahaman tentang Akhir Zaman: Suatu Refleksi Iman dan Harapan Keselamatan dalam Gereja Katolik - Putranias Zebua; Yessi Florentina Pasaribu; Anisa Putri Hulu; Kristina Enjelika Pasaribu; David Pasaribu (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines eschatology within the framework of Catholic faith as a reflection of faith and hope of salvation, not merely as a depiction of the end times. The background highlights the need to avoid reducing eschatology to a sole event of judgment day, by emphasizing the close relationship between eschatology, Christology, and soteriology, as well as the role of faith in the daily life of Catholic believers. The aim of the study is to articulate eschatology as an integrative framework that connects faith, hope, love, sacraments, liturgy, and inculturation in the Church’s praxis, and to consolidate the active participation of the faithful in the Kingdom of God, which has been initiated but not yet completed. The research method is descriptive-analytical literature review, comparing the views of experts, the Church Magisterium, and contemporary liturgical and theological documents to construct a comprehensive theoretical framework. The main findings indicate that Catholic eschatology functions as a moral and spiritual engine: (1) it integrates the “already and not yet” in the experience of faith; (2) it links eschatological hope with the actions of love, justice, and social liberation; (3) it bridges private faith with sacramental practice and inculturation. Theological and pastoral implications include strengthening faith formation, participation in liturgy, and an imaginative response to present-day social and environmental challenges. This narrative affirms a living, inclusive, and relevant eschatology for the Church’s life of faith in the contemporary era.